(untitled) (Research, Society and Development, 2021)
Products of biotic and abiotic origin are being investigated for use in pest management, many of these substances can act as resistance inducers, which induces the metabolism of enzymes involved in defense mechanisms. There is a search for efficient and alternative ways of controlling carmine cochineal (Dactylopius opuntiae Cockerell), the main pest of forage palm (Opuntia spp) in Northeast Brazil. The aim of the study was to evaluate the application of biotic and abiotic inducers on the palms to induce resistance through the activity of the antioxidant enzyme phenylalanine ammonia lyase. The experiment was carried out in a greenhouse at the Federal University of Agreste of Pernambuco, using an Completely Randomized Design (CRD), distributed in a factorial scheme (3x8x3) with three Opuntia genotypes, eight treatments: Trichoderma viride URM 6824, Trichoderma viride URM 6823, Aureobasidium pullulans URM 6874, salicylic acid, chitosan, amino butyric acid, distilled water with the insect (positive control), distilled water without the insect (negative control), with three collection periods and four repetitions. The results were subjected to analysis of variance (ANOVA), the means being compared by the Scott-Knott test at the level of 5% probability (p <0.05) and by orthogonal contrasts. The biological inducers T. viride URM 6824 and T. viride URM 6823 as well amino butyric acid influenced the increase in the enzymatic activity of phenylalanine ammonia lyase. This result demonstrates the potential for use in alternative management, and future studies are needed to deepen the applicability in field conditions.